Morphological Aspects of Intestinal Failure in Experimental Peritonitis And Correction (Texas Journal of Medical Science, 2023)
Our studies show that pathomorphological changes in the small intestine in acute experimental peritonitis are characterized by dystrophic, inflammatory-destructive and vascular disorders in the vascular tissue structures of the small intestine wall. In the pathogenesis of damage to the small intestine, deep inflammatory and destructive changes in the vessels of the microhemocirculatory bed, which subsequently lead to disruption of cell trophism, tissue hypoxia, damage to cellular elements, disruption of cellular metabolism, deficiency of energy and plastic materials, accumulation of perverted metabolic products in cells and tissues, are of great importance. . The use of the “Zerotox“ enterosorbent in the treatment complex for the treatment of endogenous intoxication and toxemia had a positive effect on the morphofunctional status of the small intestine, on the clinical course of the disease, on the composition of the intestinal microflora, indicators of local immunological protection, improved clinical and laboratory signs of endogenous intoxication, reduced the recovery period bowel function, reduced the number of postoperative complications